Combining a chaos system with an Arnold cat map for a secure authentication scheme in wireless communication networks. Issue 2 (25th February 2014) - Chen, Young-Long; Cheng, Chung-Ming
Abstract : Purpose: – Wu et al. 's scheme has a security problem that is related to anonymity: attackers can determine by interception the identity of a legal user. This paper aims to propose a new secure authentication which combines a chaos system with an Arnold cat map. The scheme improves upon that of the Wu et al. 's scheme. The scheme proposed herein provides for full anonymity and improves the security of authentication messages for wireless communications. Design/methodology/approach: – A novel scheme that integrates a chaos sequence is used with an Arnold cat map for authentication messages. Authentication messages are shuffled using an Arnold cat map to improve the security of authentication in wireless communications. An analytic approach based on a chaos sequence with an Arnold cat map is developed to secure authentication. The proposed scheme is presented in this study to overcome the inherent drawbacks of existing designs. Findings: – The integrated scheme involves two steps. First, a chaos map is used to generate a set of chaos sequences that is added to the authentication messages. Second, the authentication messages are shuffled using an Arnold cat map. The main feature of the proposed design is such that the chaos systems are sensitive to the initial values of conditions. Sensitivity will lead to long-term behavior unpredictability to reflect the non-linear dynamic systems. Furthermore, to increase the complexity of the authentication message, the authors also use an Arnold cat map. Originality/value: – The proposed scheme provides functions that include full anonymity properties, protection of the real identity of the user, one-time password properties, timestamp benefits and sufficient complexity of the password. The analysis shows that the proposed scheme exhibits the advantages of the chaos system and is more secure than previous schemes. Notably, the proposed scheme is effective for wireless communications.